Effects of COVID-19 on Gifted Students’ Quality of Life (QOL-GSS): Scale Development and Application - Nihan Potas; Şuay Nilhan Açıkalın; Nilüfer Koçtürk; Sema Abal; Şefika Şule Erçetin (Sakarya University Journal of Education)
The aim of this study is to develop a valid and reliable scale to measure the effects of COVID-19 on gifted students’ quality of life and analyse its effects on their quality of life considering some variables such as gender, age, education level, mother’s education level, father’s education level, monthly income and number of children in the family. To this end, a scale was developed and its reliability and validity were measured through a number of measures. The internal consistency was used to evaluate the reliability of the scale whereas its validity was analyzed by a factor analysis. Regarding EFA, the result of the KMO test was .90 and Bartlett test χ2 statistic was 3055.306 (p < .001). Path coefficients of the items varied between .55 and .89 and Cronbach’s Alpha (α=.76) coefficients indicated that the data obtained from the scale (QOL-GSS) was reliable. Results overall indicated that COVID-19 affected gifted students’ quality of life slightly in all dimensions and QOL-GSS. Results also indicated that the effect of COVID-19 on gifted students’ quality of life showed significant differences by gender, education level, mother’s education level, father’s education level, monthly income and number of children in the family.